The I and the Other (Lenora) in the Poetry of Joseph III (Journal of the College of Education for Women, 2022)
A literary text is not void of the use of the ego and the other while speaking or in a spoken communication. Such a usage is apparently outstanding in Arabic literature, and it reflects society in all its various cultural, social and political conditions. Therefore, the ego is one of the prominent concepts on which human personality is built, and its role in the formation of society and in communicating among all human societies. Accordingly, the present paper aims to clarify the duality of the ego and the other, where the ego starts from the poet himself to expand the circle of subjectivity by including his family, society, immediate surroundings, race and his religion. The other, on the other hand, that is separated from the poet, represents the family, tribe, gender and religion. All such references are found in Lenora’s personality. The latter differed from the poet with respect to his family, tribe, sex, and religion. Thus, the significance of the study lies in finding the link between this duality. The study has concluded that highlighting the ego to the other side, and to the poet’s personality was reflected in his poetic production by highlighting the ego even when talking about the other. Such a feature characterizes the king, who has the authority. The study has further concluded that Joseph's love for Lenora constitutes a qualitative step and a new trend of the flirting art in Andalusia, creating as a result a new civilized atmosphere, expressing the spirit of the new civilized life. Accordingly, the researcher adopted the descriptive analytical approach to reveal the role of ego alongside the other (Linora) while studying and analyzing the data. The study has finally concluded that the ego and the other are dual in the poetry of Linora where imagination participates in the formation of an image. Besides, the Poet, Joseph III has drawn the ego to express what he was aware of in terms of feelings, sense and sincerity in expressing and influencing the listener or the recipient, highlighting the active ego linguistically, drawing its image, and demonstrating the way the ego possesses a self-referral that cannot be escaped from.